Effects of physical exercise on Irisin and BDNF concentrations, and their relationship with cardiometabolic and mental health of individuals with Metabolic Syndrome: A Systematic Review - Wilder Villamil-Parra; Luisa Moscoso-Loaiza (Experimental Gerontology)
Chronic Non-Communicable Diseases (NCDs), including cardiovascular diseases, cancer, chronic respiratory diseases, and diabetes, are the leading global causes of mortality, accounting for 71 % of deaths annually. Metabolic Syndrome (MS), characterized by hypertension, obesity, insulin resistance, and dyslipidemia, is a significant risk factor for NCDs. Physical inactivity exacerbates these conditions, contributing to poor cardiovascular and mental health outcomes. Objective: To analyze the effects of physical exercise on Irisin and Brain-Derived Neurotrophic Factor (BDNF) concentrations and their relationship with cardiometabolic and mental health of individuals with MS. Methods: A systematic review was conducted of articles published between August 2023 and June 2024 in ScienceDirect, PubMed, and SciELO, following PRISMA guidelines. Inclusion criteria encompassed observational studies, clinical trials, and reviews with high methodological quality. The review focused on Irisin, BDNF, physical exercise, and MS. Results: A total of 584 articles were identified, with 43 selected for detailed analysis. The review highlights that physical exercise significantly impacts Irisin and BDNF levels, which in turn influence metabolic and mental health. Irisin, a myokine secreted during exercise, promotes the conversion of white adipose tissue to brown adipose tissue, enhancing energy expenditure and metabolic health. Elevated Irisin levels are associated with improved cognitive function and mental well-being. BDNF, a neurotrophin, supports neuronal growth and cognitive function. Exercise-induced increases in BDNF levels are linked to enhanced neuroplasticity, reduced anxiety, and improved mood. Conclusion: Understanding the role of Irisin and BDNF in response to physical exercise offers valuable insights for developing strategies to manage and prevent MS and its related mental health issues. Further research is needed to elucidate the molecular mechanisms involved.